Eggcellent Adventures in Classroom Embryology: An Intracurricular Guide to Chicken Embryology - Shaina Spann; Judy Levings (EDIS)
In most cases, when a teacher signs up to teach chicken embryology in the classroom, the teacher sets up the incubator and the teacher and class wait for the eggs to hatch. That is the experience. But the daily plan of lessons in this guide makes the chicken embryology experience an intracurricular experience. Through a series of activities, students can see firsthand how a chicken develops in an egg. Students will candle eggs to observe chick development, record data, make predictions, and conclude what they think the final outcome will be. The lessons in the guide follow Florida Sunshine State Standards and each contains an experience, instructions, background information, and reflection questions. The 31 lessons address math, language arts, and visual arts, in addition to agricultural literacy and science concepts. Written by Shaina Spann and Judy Levings, and published by the 4-H Youth Development Program, November 2015.